The evaluation of hexachlorobenzene (HCB) dechlorination potential of indigenous anaerobes from river sediments a thesis - Dellosa, Dorothy Macanas (2007)
The role of indigenous anaerobes was evaluated for its dechlorination ability to degrade hexachlorobenzene (HCB). Under the Stockholm Convention initiated by the United Nations Environment Programme (UNEP), HCB has been identified as one of the persistent organic pollutants (POPs) and has become a worldwide concern due to their toxicity, resistance to biodegradation and tendency to accumulate. Reductive dechlorination which is effectively known as a means of bioremediation process was conducted to test the inherent dechlorinating microbes from two different locations of river sediments. Er-Ren River and Ho-Tsin River of southern Taiwan. This study aimed to provide information on the characteristics and behavior of microbial activity as well as the dechlorination potential under different mediums, effect of enrichment, acclimation, microbial succession and replenishment. After 70 days of incubation, there was an evident lag phase and no dechlorination was observed from the medium using sediment water as compared to sedmient slurry sample sets. A similar dechlorination pathway was observed having a major pathway vcia 1,2,4-tetrachlorobenzene (1,2,4-TCB) showed trace amounts for dechlorination of DCBs. The results also showed that through the years of progressive research from this site locations, there is a diminishing capability of the dechlorinating anaerobes inhabiting within Er-Ren River. Correlating from the data of previous works of the same source locations, a remarkable finding was established which may predict the fate and transport of this chlorinated compound in the environment.